Electrospinning of Poly[acrylonitrile‐co‐(glycidyl methacrylate)] Nanofibrous Mats for the Immobilization of Candida Antarctica Lipase B - Dai, Tianhe; Miletić, Nemanja; Loos, Katja; Elbahri, Mady; Abetz, Volker (Macromolecular Chemistry and Physics, 2010)
Abstract PANGMA nanofibers and nanomats with fiber diameters of 200–300 nanometers were fabricated by electrospinning. Cal‐B was covalently immobilized onto the PANGMA nanomats via three different immobilization routes. The properties of the Cal‐B‐immobilized PANGMA nanomats were assayed and compared with the free Cal‐B. The observed Cal‐B loading on these nanomats is up to ≈50 mg · g −1 , and their hydrolytic activity is up to ≈2 500 nmol · min −1 · mg −1 , much higher than free enzyme powder and also slightly higher than Novozyme 435. Cal‐B immobilized PANGMA nanomats have better reusability, thermal stability, and storage ability than free Cal‐B. They retain over 50% of their initial activity after 15 cycles, over 65% after 10 h heat incubation, and over 75% after 30 d storage. magnified image